PEMBUATAN RECYCLE PLASTIK HDPE SEDERHANA MENJADI ASBAK - Anis Masyruroh; Iroh Rahmawati (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Plastic is a commodity that is often used in everyday life. Almost all equipment or products used are made of plastic and are often used as packaging for raw materials. But in reality, plastic waste is a global environmental problem because plastic takes a long time to undergo the recycling process. The types of plastics are PET (Polyethylene Terephtalate), HDPE (High Density Polyethylene), V (PlyvinylChloride), LDPE (Low Density Polyethylene), PP (Polypropylene), PS (Polytyrene), and OTHER. Plastic waste has a bad impact on the environment because of the nature of plastic which is difficult to decompose naturally by the soil, even though it has been buried for hundreds of years. Recycling HDPE plastic into an ashtray is done because of the large piles of plastic waste that are increasingly unsettling, causing disease, reducing soil fertility, and damaging ecosystems on land and in the oceans. After conducting research on the recycle of HDPE plastic into an ashtray, the results were uneven and there were still empty spaces in the printed results. The use of color in making recycles is very influential to make the appearance of plastic more attractive.